Genetic Study of Primary Dystonias: Recommendations from the Centro Hospitalar São João Neurogenetics Group - Monteiro, Ana; Massano, João; Leão, Miguel; Garrett, Carolina; Grupo de Neurogenética do Centro Hospitalar São João, Em nome do (Acta Médica Portuguesa, 2017)
The primary dystonias are a particular group of dystonias of presumed genetic origin, with a wide age of onset and variable progression. The diagnosis is, therefore, a challenge and the issue of the genetic investigation presents frequently in clinical practice. In the past few years several gene mutations have been identified as causative of primary dystonias. The choice of molecular testing is complex, given the clinical specificities and low frequency of these entities and the cost of genetic testing. It must follow observation by specialized clinicians highly differentiated in this area and be supported by a rational plan of investigation. The Centro Hospitalar São João Neurogenetics Group, a multidisciplinary team of Neurologists and Geneticists with special interest in neurogenetic disorders, devised consensus recommendations for the investigation of the genetic etiology of the primary dystonias, based on international consensus documents and recent published scientific evidence. This manuscript adopts the new classification system for genetic movement disorders, allowing for its systematic and standardized use in clinical practice.